Thermochemical measurement of the ligand field splitting energies for hexaammine complexes of Mn(II), Fe(II), and Zn(II) - Badri, M.; Jamieson, J. W. S. (NRC Research Press, 1977)
Various lower ammines and high-energy modifications of lower ammines of the sulphates of Mn(II), Fe(II), and Zn(II) have been prepared and their heats of solution have been measured. For each of these ammine systems, the maximum difference in heat of solution, expressed in kcal/mol of heptaammine, has been found to be of the right order of magnitude to be regarded as the ligand field splitting energy for the hexaammine complex of the metal ion